Genetic Variation and Population Genetics of Taenia saginata in North and Northeast Thailand in relation to Taenia asiatica - Malinee Anantaphruti; Urusa Thaenkham; Teera Kusolsuk; Wanna Maipanich; Surapol Saguankiat; Somjit Pubampen; Orawan Phuphisut (Journal of Parasitology Research)
Taenia saginata is the most common human Taenia in Thailand. By cox1 sequences, 73 isolates from four localities in north and northeast were differentiated into 14 haplotypes, 11 variation sites and haplotype diversity of 0.683. Among 14 haplotypes, haplotype A was the major (52.1%), followed by haplotype B (21.9%). Clustering diagram of Thai and GenBank sequences indicated mixed phylogeny among localities. By MJ analysis, haplotype clustering relationships showed paired-stars-like network, having two main cores surrounded by minor haplotypes. Tajima’s D values were significantly negative in T. saginata world population, suggesting population expansion. Significant Fu’s Fs values in Thai, as well as world population, also indicate that population is expanding and may be hitchhiking as part of selective sweep. Haplotype B and its dispersion were only found in populations from Thailand. Haplotype B may evolve and ultimately become an ancestor of future populations in Thailand. Haplotype A seems to be dispersion haplotype, not just in Thailand, but worldwide. High genetic T. saginata intraspecies divergence was found, in contrast to its sister species, T. asiatica; among 30 samples from seven countries, its haplotype diversity was 0.067, while only 2 haplotypes were revealed. This extremely low intraspecific variation suggests that T. asiatica could be an endangered species.